2003
DOI: 10.2355/isijinternational.43.807
|View full text |Cite
|
Sign up to set email alerts
|

Initial Solidification Control of Continuous Casting Using Electromagnetic Oscillation Method

Abstract: An initial solidification control technology, called the Electromagnetic Oscillation Method, intermittently applying high frequency magnetic field was developed aiming to reduce the friction between mold and initial solidified shell and to perform high speed casting for producing cast having excellent surface properties. According to the method, a high frequency magnetic field is applied synchronizing with the mold oscillation, applying a horizontal and inward electromagnetic force from outside the mold during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Reported thicknesses of the mold flux film are in the range of a few hundreds of microns to a few millimeters. [16][17][18][19][20][21][22][23][24][25][26][27][28] Hanao et al developed mold fluxes for high-speed continuous casting of a hypo-peritectic steel slab, and investigated the thickness of the mold flux based on CaF2-and Na2O-containing calcium silicates below the meniscus. They reported that the film thickness of the mold fluxes was found to be 0.8-1.6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Reported thicknesses of the mold flux film are in the range of a few hundreds of microns to a few millimeters. [16][17][18][19][20][21][22][23][24][25][26][27][28] Hanao et al developed mold fluxes for high-speed continuous casting of a hypo-peritectic steel slab, and investigated the thickness of the mold flux based on CaF2-and Na2O-containing calcium silicates below the meniscus. They reported that the film thickness of the mold fluxes was found to be 0.8-1.6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the solidified shell thickness is almost decreased linearly with increasing exciting current density. Under the condition that the exciting current density is less than 4?62610 7 A m 22 , if the exciting current density is increased by 6?6610 6 A m 22 , the solidified shell is thinned 1?2-1?4 mm. Whereas if the exciting current density exceeds 4?62610 7 A m 22 , the solidified shell is thinned 2?2-2?3 mm with exciting current density increased by 6?6610 6 A m 22 .…”
Section: Effect Of Exciting Current Density On Solidificationmentioning
confidence: 99%
“…1,2 Electromagnetic continuous casting minimises the occurrence of casting defects on the surface and subsurface of billets by exerting an alternating electromagnetic field in the initial solidification region of molten steel in the mould to form a thin and uniform early solidified shell. 3,4 This is achieved by the electromagnetic force and induction heat of electromagnetic field at the meniscus in the mould. 5 The electromagnetic force can decrease the contact pressure between the mould wall and molten steel or initial solidified shell so that the adverse effects of mould oscillation on billet surface quality are reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) Several kinds of alternative magnetic field in terms of their amplitude have been tested in this technology, such as, intermittent, [3][4][5][6] half-triangle 7) and quasi-sinusoidal 8) ones. On the base of these studies, a novel technology named Mould Oscillation-Less Electromagnetic Continuous Casting (MOLECC) Process 4,9) has been proposed in order to substitute the huge and heavy mechanical mould oscillation system by a small and light electromagnetic one.…”
Section: Introductionmentioning
confidence: 99%